Pengaruh Gaya Belajar Siswa terhadap Hasil Belajar Pendidikan Agama Islam - rafiqa sari (IQRO: Journal of Islamic Education, 2019)
Research aims to understand a style learning and study results style and influence in the learning student learning islamic education x a state sma palopo 4. Type this study quantitative with the design ex-post facto capital with a population of 51 students with the sample is covering sampling.Data drawn through the survey data processed by analysis descriptive statistics and statistics inferential.The research results show that study visual style, auditory, students and a kinesthetic having influence in the the highest student learning study visual style of 13,2 %.Religious education study results people in the 28 people and frequency the 55 % the percentage.And influence the style of student learning islamic education in the learning supported by r2 ( r square) of 0,360 or 36 % style learning in the learning student effect for  islamic education.